Application of superelements in static analysis of thin‐walled structures - Kreja, Ireneusz; Mikulski, Tomasz; Szymczak, Czeslaw (Journal of Civil Engineering and Management, 2004)
A concept of a beam superelement is suggested as a new tool in the static analysis of structures made of thin‐walled members. This proposal seems to be especially attractive for treating the problems where the existing one‐dimensional models do not provide proper solutions. This class of problems includes, for instance, the torsion of thin‐walled beams with battens and the determination of the bimoment distribution at the nodes of frames made of thin‐walled members. The entire segment of the thin‐walled beam with warping stiffener or the whole node of the frame is modelled with shell elements. The stiffness matrix of such thin‐walled beam superelement can be estimated according to the standard procedure of the enforced unit displacements. The accuracy of the proposed one‐dimensional model has proved to be comparable to that offered by the detailed FEM model where the whole structure is represented by a very large number of shell elements. First Published Online: 14 Oct 2010